Enhancement of low-density polyethylene biodegradation through the production of surface-active compounds by Pluralibacter gergoviae TYB1 - Nalini Soni; Vinoth Kumarasamy; Priya Gupta; Sangeeta Devendra Kumar Singh; Chinnaperumal Kamaraj; Vetriselvan Subramaniyan; Silambarasan Tamil Selvan; Rajesh Kannan Velu; Balasubramanian Velramar (Scientific Reports)
Abstract Pluralibacter gergoviae TYB1 is a facultative anaerobic bacterium with a high efficiency of low-density polyethylene (LDPE) degradation using self-producing surface-active compounds (SACs). This bacterium was used for the degradation of LDPE. In this study, analysis was performed to check the SAC production efficiency of P. gergoviae TYB1 by drop collapse assay, oil displacement test, emulsification index, and foamability testing. RSM was performed to scale up the production of SAC for its further utilization for experimental purposes to improve the biofilm formation of P. gergoviae TYB1 on LDPE. SAC extracted from the broth supernatant was subjected to FT-IR, TLC, and GC-MS analyses. Within 30 days of LDPE treatment along with bacteria and SAC, bacterial SAC improved biofilm formation and biodegradation of the LDPE film by P. gergoviae TYB1. The results were showed decreased hydrophobicity and improved biofilm formation on the LDPE films. LDPE degradation was measured using weight loss analysis, FTIR, and SEM. The results were indicated that LDPE degradation was enhanced by up to 17.5% without any pre-treatments for 30 days of treatment with P. gergoviae TYB1 and SAC. SAC was enhanced biofilm production on LDPE and improved biodegradation of LDPE by P. gergoviae TYB1 was confirmed.